Pemahaman dan Pengaturan Peran Organisasi Advokat di Indonesia Dalam UU No 18 Tahun 2003 tentang Advokat - Erika Nurul Hidayah; Mawaddah Permatasari; Fauziah Lubis (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This study aims to determine the formation of Advocate Organizations in Indonesia as mandated in Law Number 18 of 2003 concerning Advocates, in fact it has caused a polemic regarding which Advocate Organizations are recognized by the law. As it is known that the 1945 Constitution has provided fundamental protection for freedom of association and assembly, the provisions of that article provide a constitutional basis that every Advocate actually has the right to establish more than one Advocate Organization, so from this it was found a misunderstanding in the Advocate Law, which confuses the notion of an organization and its formation with what is the true meaning of the purpose of establishing a single forum in the Advocate profession. This paper is intended so that the formation of this single forum does not lead to conflicts of struggle between Advocates without prejudice to the freedom and independence of Advocates which is in line with the goals of a modern democratic rule of law which requires the role of the government in the formation of this single forum. Keywords: Understanding, Setting, Organization